4.3.2.15 Bessel form A type ode ay+by+(cerxm)y=f(x)
4.3.2.15.1 Example ay+by+(cerxm)y=0

ode internal name "second_order_bessel_ode_form_A"

These are ode of the above form which can be converted to Bessel using transformation x=ln(t).

4.3.2.15.1 Example ay+by+(cerxm)y=0 An ode of the form

(1)ay+by+(cerx+m)y=0

can be transformed to Bessel ode using the transformation

x=ln(t)ex=t

Where a,b,c,m are not functions of x and where b and m are allowed to be be zero. Using this transformation gives

dydx=dydtdtdx=dydtex(2)=tdydt

And

d2ydx2=ddx(dydx)=ddx(tdydt)=ddtdtdx(tdydt)=dtdxddt(tdydt)=tddt(tdydt)(3)=t(dydt+td2ydt2)

Substituting (2,3) into (1) gives

at(dydt+td2ydt2)+btdydt+(cerx+m)y=0(aty+at2y)+bty+(ctr+m)y=0at2y+(b+a)ty+(ctr+m)y=0(4)t2y+b+aaty+(catr+ma)y=0

Which is Bessel ODE. Comparing the above to the general known Bowman form of Bessel ode which is

(C)t2y+(12α)ty+(β2γ2t2γ(n2γ2α2))y=0

And now comparing (4) and (C) shows that

(5)(12α)=b+aa(6)β2γ2=ca(7)2γ=r(8)(n2γ2α2)=ma

(5) gives α=12b+a2a. (7) gives γ=r2. (8) now becomes (n2(r2)2(12b+a2a)2)=ma or n2=ma+(12b+a2a)2(r2)2. Hence n=2rma+(12b+a2a)2 by taking the positive root. And finally (6) gives β2=caγ2 or β=ca1γ=ca2r (also taking the positive root). Hence

α=12b+a2an=2rma+(12b+a2a)2β=ca2rγ=r2

But the solution to (C) which is general form of Bessel ode is known and given by

y(t)=tα(c1Jn(βtγ)+c2Yn(βtγ))

Substituting the above values found into this solution gives

y(t)=t12b+a2a(c1J2rma+(12b+a2a)2(ca2rtr2)+c2Y2rma+(12b+a2a)2(ca2rtr2))

Since ex=t then the above becomes

y(x)=ex(12b+a2a)(c1J2rma+(12b+a2a)2(ca2rexr2)+c2Y2rma+(12b+a2a)2(ca2rexr2))=ex(b2a)(c1J2rma+(b2a)2(ca2rexr2)+c2Y2rma+(b2a)2(ca2rexr2))=ex(b2a)(c1J2rma+b24a2(ca2rexr2)+c2Y2rma+b24a2(ca2rexr2))=ex(b2a)(c1J2r4ma+b24a2(ca2rexr2)+c2Y2r4ma+b24a2(ca2rexr2))(9)=ex(b2a)(c1J1ra4ma+b2(ca2rexr2)+c2Y1ra4ma+b2(ca2rexr2))

Equation (9) above is the solution to ay+by+(cerx+m)y=0. Therefore we just need now to compare this form to the ode given and use (9) to obtain the final solution. Let us now apply this to an example for illustration. Given the ode

y+(e2x4)y=0

Comparing the above to ay+by+(cerx+m)y=0 shows that a=1,b=0,c=1,r=2,m=4. Hence the solution (9) becomes

y(x)=ex(b2a)(c1J1ra4ma+b2(ca2rexr2)+c2Y1ra4ma+b2(ca2rexr2))=c1J1216(ex)+c2Y1216(ex)=c1J2(ex)+c2Y2(ex)=c1BesselJ(2,ex)+c2BesselY(2,ex)

Another example for illustration. Given the ode

y+y+(ex4)y=0

Comparing the above to ay+by+(cerx+m)y=0 shows that a=1,b=1,c=1,r=1,m=4. Hence the solution (9) becomes

y(x)=ex(12)(c1J16(2ex12)+c2Y16+1(2ex12))=ex2(c1J17(2ex2)+c2Y17(2ex2))

Another example for illustration. Given the ode

y+(e2xn2)y=0

Comparing the above to ay+by+(cerx+m)y=0 shows that a=1,b=0,c=1,r=2,m=n2. Hence the solution (9) becomes

y(x)=ex(b2a)(c1J1ra4ma+b2(ca2rexr2)+c2Y1ra4ma+b2(ca2rexr2))=c1J124(n2)(ex)+c2Y124(n2)(ex)=c1Jn(ex)+c2Yn(ex)=c1BesselJ(n,ex)+c2BesselY(n,ex)